2018
DOI: 10.1096/fj.201701008r
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic factor imbalance precedes complement deposition in placentae of the BPH/5 model of preeclampsia

Abstract: Preeclampsia (PE), a hypertensive disorder of pregnancy, is a leading cause of maternal and fetal morbidity and mortality. Although the etiology is unknown, PE is thought to be caused by defective implantation and decidualization in pregnancy. Pregnant blood pressure high (BPH)/5 mice spontaneously develop placentopathies and maternal features of human PE. We hypothesized that BPH/5 implantation sites have transcriptomic alterations. Next-generation RNA sequencing of implantation sites at peak decidualization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 79 publications
(109 reference statements)
8
52
0
Order By: Relevance
“…We previously showed that adult, nonpregnant BPH/5 female mice exhibit increased body weight and proinflammatory reproductive WAT (i.e., TNF-α) compared to controls [17], which persists in early pregnancy (e7.5) [14]. At that time, the maternal-fetal interface in BPH/5 mice is characterized by an overexpression of inflammatory mediators, including C3 and CfB but not C1qa, which is associated with an angiogenic imbalance [7]. We hypothesized that increased reproductive WAT could be a source of complement factors and, if reduced by maternal weight loss, would improve the angiogenic imbalance in BPH/5 implantation sites at e7.5, the peak of decidualization prior to placenta formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously showed that adult, nonpregnant BPH/5 female mice exhibit increased body weight and proinflammatory reproductive WAT (i.e., TNF-α) compared to controls [17], which persists in early pregnancy (e7.5) [14]. At that time, the maternal-fetal interface in BPH/5 mice is characterized by an overexpression of inflammatory mediators, including C3 and CfB but not C1qa, which is associated with an angiogenic imbalance [7]. We hypothesized that increased reproductive WAT could be a source of complement factors and, if reduced by maternal weight loss, would improve the angiogenic imbalance in BPH/5 implantation sites at e7.5, the peak of decidualization prior to placenta formation.…”
Section: Discussionmentioning
confidence: 99%
“…An angiogenic imbalance in early pregnancy characterizes BPH/5 mice and other models of PE [1,7]. Complement inhibition was shown to restore placental VEGF levels in BPH/5 placenta [15].…”
Section: A Reduction In Bph/5 Maternal Adiposity Lowers C3 and Restormentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the placenta itself also synthesizes a variety of hormones, enzymes, and cytokines, which are mostly encoded by placenta‐specific genes, to adjust placental physiology and mediate gas exchange, nutrient uptake, and waste elimination between the mother and fetus (Bu, Alam, Dhakal, Vivian, & Soares, ; Burton & Fowden, ; Naruse et al, ; Simmons, Rawn, Davies, Hughes, & Cross, ). Emerging evidence suggests that some internal or external factors can target certain placenta‐specific genes, and therefore may impair placenta formation and function, ultimately contributing to the etiology of many pregnancy‐related diseases such as pre‐eclampsia, intrauterine growth restriction, and abortion; this can have consequences for the long‐term health of the individual (Huynh, Dawson, Roberts, & Bentley‐Lewis, ; Kenchegowda, Natale, Lemus, Natale, & Fisher, ; Sones et al, ). Thus, decoding the functions of these placental genes will help to elucidate placental physiology and pregnancy‐related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…the long-term health of the individual (Huynh, Dawson, Roberts, & Bentley-Lewis, 2015;Kenchegowda, Natale, Lemus, Natale, & Fisher, 2017;Sones et al, 2018). Thus, decoding the functions of these placental genes will help to elucidate placental physiology and pregnancy-related diseases.…”
mentioning
confidence: 99%